2009
DOI: 10.1080/10641950802601179
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Serum CRP, IL-6, TNF-α, Homocysteine, Folic Acid and Vitamin B12 Levels with the Severity of Preeclampsia and Fetal Birth Weight

Abstract: Elevated maternal serum levels of hs-CRP, TNF- alpha, IL-6 and homocysteine in preeclamptic women correlate with fetal birth weight in the early third trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 26 publications
7
100
7
1
Order By: Relevance
“…Several studies have demonstrated a shift from Th2 to Th1 in preeclampsia with an increase of pro-inflammatory and a decrease of antiinflammatory cytokines (12,(21)(22)(23). We failed to demonstrate this suggested shift by mere cytokine analysis, although levels of the Th2 cytokine IL-4 were decreased in preeclamptic women.…”
Section: Discussioncontrasting
confidence: 62%
“…Several studies have demonstrated a shift from Th2 to Th1 in preeclampsia with an increase of pro-inflammatory and a decrease of antiinflammatory cytokines (12,(21)(22)(23). We failed to demonstrate this suggested shift by mere cytokine analysis, although levels of the Th2 cytokine IL-4 were decreased in preeclamptic women.…”
Section: Discussioncontrasting
confidence: 62%
“…Thirty‐two studies in total reported on C‐reactive protein levels,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 of which 17 were applicable for meta‐analysis 21, 22, 23, 29, 30, 31, 32, 33, 34, 37, 38, 39, 41, 42, 47, 49, 50. A significantly higher C‐reactive protein was found in women with pre‐eclampsia than in non‐hypertensive controls ( Figure 2), and this correlation was stronger in severe than in mild pre‐eclampsia ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…An interventional trial has demonstrated that folate supplementation in the second trimester of pregnancy significantly reduces both serum homocysteine levels and the risk of preeclampsia 23 . Markedos et al 6 , Braekke et al 10 and Guven et al 24 , studies showed that maternal circulating concentrations of vitamins B12 and folic acid are not significantly different in hyperhomocysteinemic preeclamtic group compared with normal pregnant women. Lopez et al 7 found that the levels of homocysteine and folate are increased in preeclampsia, but values of vitamin B12 are not changed compared with normal pregnancy.…”
Section: Discussionmentioning
confidence: 97%